The Influence of EEG References on the Analysis of Spatio-Temporal Interrelation Patterns - Ríos-Herrera, Wady A.; Olguín-Rodríguez, Paola V.; Arzate-Mena, J. Daniel; Corsi-Cabrera, Maria; Escalona, Joaquín; Marín-García, Arlex; Ramos-Loyo, Julieta; Rivera, Ana Leonor; Rivera-López, Daniel; Zapata-Berruecos, José F.; Müller, Markus F. (Frontiers in Neuroscience, 2019)
The characterization of the functional network of the brain dynamics has become a prominent tool to illuminate novel aspects of brain functioning. Due to its excelent time resolution, such research is oftentimes based on electroencephalographic recordings (EEG). However, a particular EEG-references might cause crucial distortions of the spatio-temporal interrelation pattern and may induce spurious correlations as well as diminish genuine interrelations originally present in the dataset. Here we investigate in which manner correlation patterns are affected by the EEG reference. To this end we probe the influence of 7 popular reference schemes on artificial recordings derived from well controlled numerical test frameworks. In this respect we are not only interested in the deformation of spatial interrelations, but we test aditionally in which way the time evolution of the functional network, estimated via some bi-variate interrelation measure, gets distorted. It turns out that the median reference shows best performance in most situations considered in the present study. However, if a collective brain dynamics has to be expected, where most of the signals get correlated, also this scheme may cause crucial deformations of the functional network, such that the parallel use of different reference schemes seems advisable.